The old and the new Andean philosophy. A critique of Josef Estermann - Hernández Soto, Javier Eduardo (2022)
Postmodernity opens new discursive sources that tend to relativize the areas of philosophical knowledge, is the case of Andean philosophy, harshly questioned in its genesis and development. Faced with this situation, various positions arise on the subject in question, being that of Josef Estermann the most outstanding, characterized by trying to get rid of Eurocentrism and colonial perspectives established by the canonical tradition. Despite the above, Estermann’s work (Filosofía Andina. Estudio intercultural de la sabiduría autóctona andina), is based on objectionable categories such as: metaphysics, humanism and hyperbolization of philosophy; for this reason, his project is an attempt to insert old canons into a contemporary intercultural project. For this reason, the present investigation considers the need to postulate a second sense or perspective of Andean philosophy, a sense that emphasizes the interpretation of all the spiritual creations of the Andean man, in other words, that does not attend to the Andean culture itself, as Estermann suggests, but to the philosophical gaze that is launched on it, resulting in an interpretation and not an attempt to incarnate the runes. Thus, this new meaning includes profiles, genealogies and scope that allow evaluating the possibilities of its development and future in general.